Employing Theatrical Games to Establish and Support Onlife Learning Communities on Mathematical Principles of Informatics - Moumoutzis, Nektarios; Apostolos Rigas, Nikolaos; Xanthaki, Chara; Maragkoudakis, Yiannis; Christodoulakis, Stavros; Paneva-Marinova, Desislava; Pavlova, Lilia (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2020)
This paper presents how the PerFECt Framework for establishing and sustaining learning communities can be combined with innovative approaches of teaching mathematics using drama, to develop unplugged activities to introduce the binary system in primary and secondary school students. The resulting Human Calculator theatrical game enables students, using their bodies, to learn the binary representation of numbers and discover the algorithms of addition, subtraction, multiplication and division.